An Experimental Study on the Seismic Performance of High-Strength Composite Shear Walls - Gan, Min; Yu, Yu; Zhang, Huakun (Frontiers in Materials, 2021)
In order to study the seismic performance of the high-strength concrete composite shear walls with embedded steel strips, four tests of the high-strength concrete composite shear walls with embedded steel strips (SPRCW-1 to SPRCW-4) are constructed and tested. According to the test results, this paper discusses the hysteresis curve, backbone curves and strain of steel plate and distributed reinforcement of high-strength concrete mid-rise and high-rise composite shear walls with embedded steel strips under different steel ratio and different steel strip positions. The test results show that in the high-strength composite shear walls with embedded steel strips, the ductility of the test specimen can be effectively improved when the ratio of the steel strip reaches a certain level. When the embedded steel strip is placed on both sides of the walls, the steel strip can better play its role. The ultimate displacement is better than when the steel strip is placed in the middle of the walls, which can effectively improve the seismic performance of the walls. The scheme with embedded steel strips is more convenient and economical for construction, which is suitable for popularization and application in middle-high buildings in highly seismic regions.